MicroRNA-532-3p Suppresses Malignant Behaviors of Tongue Squamous Cell Carcinoma via Regulating CCR7 - Feng, Cuijuan; So, Hyon Il; Yin, Shoucheng; Su, Xingzhou; Xu, Qiang; Wang, Simin; Duan, Weiyi; Zhang, Enjiao; Sun, Changfu; Xu, Zhongfei (Frontiers in Pharmacology, 2019)
To provide better therapeutic avenues for treating tongue squamous cell carcinoma (TSCC), a series of experiments about the effects of microRNA (miR)-532-3p on TSCC malignant behaviors were carried out. The result showed that miR-532-3p was down-regulated and C-C chemokine receptor 7 (CCR7) was up-regulated in the tumor tissues compared with those in the paired paratumor tissues. Further, expression of miR-532-3p was detected in four TSCC cell lines, TSCCA, TCA8113, CAL-27, and SCC-25. The miR-532-3p mimics and inhibitor were transfected into the CAL-27 and TCA8113 cell lines which were relatively lowest and highest miR-532-3p expression, respectively. It was found that the overexpression of miR-532-3p suppressed TSCC cell proliferation, migration, invasion, and promoted apoptosis in vitro, whilst knockdown of miR-532-3p was reversed these behaviors. The bioinformatics predicted that CCR7 was a downstream gene of miR-532-3p, which was confirmed via luciferase assay. Following, the decline of CCR7 in the miR-532-3p mimics group and the rise of CCR7 in the miR-532-3p inhibitor group were also verified. In addition, enhanced cell proliferation, migration and invasion induced by CCR7 were partly restrained by miR-532-3p in TSCC cell. Meanwhile, miR-532-3p attenuated tumourigenesis in vivo due to the reduction of tumor volume and Ki-67 positive rate as well as the increase of apoptotic cells. Taken together, these findings reveal a pivotal role for miR-532-3p/CCR7 axis in regulating TSCC, and this novel axis could be suitable for therapeutic intervention in TSCC disease.